Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/biology10121279
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Armenian Grapevine (Vitis vinifera L.) Germplasm: Molecular Characterization and Parentage Analysis

Abstract: Armenia is an important country of origin of cultivated Vitis vinifera subsp. vinifera and wild Vitis vinifera subsp. sylvestris and has played a key role in the long history of grape cultivation in the Southern Caucasus. The existence of immense grapevine biodiversity in a small territory is strongly linked with unique relief and diverse climate conditions assembled with millennium-lasting cultural and historical context. In the present in-depth study using 25 nSSR markers, 492 samples collected in old vineya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…The establishment of germplasm collections and the preservation of their richness require the use of both types of markers (morphological and molecular) for the correct identification of each accession and the efficient use of the preserved diversity. As with many other authors (Martinez et al 2003;Stavrakaki & Biniari 2017;Margaryan et al 2021), our results demonstrated the effectiveness of the ampelographic and molecular methods for assessing the genetic diversity among the grapevine accessions. Each type of marker, analysed by appropriate mathematical methods, brings additional and complementary information, which contributes to the correct assessment of the intra-and inter-varietal diversity of the grapevine genetic resources.…”
Section: Resultssupporting
confidence: 88%
“…The establishment of germplasm collections and the preservation of their richness require the use of both types of markers (morphological and molecular) for the correct identification of each accession and the efficient use of the preserved diversity. As with many other authors (Martinez et al 2003;Stavrakaki & Biniari 2017;Margaryan et al 2021), our results demonstrated the effectiveness of the ampelographic and molecular methods for assessing the genetic diversity among the grapevine accessions. Each type of marker, analysed by appropriate mathematical methods, brings additional and complementary information, which contributes to the correct assessment of the intra-and inter-varietal diversity of the grapevine genetic resources.…”
Section: Resultssupporting
confidence: 88%
“…The archaeological record suggests that grapevine domestication began in southeastern Anatolia (the Asian part of Türkiye) or the region known as Transcaucasian about 6000 to 7000 years ago before grapevine cultivars spread throughout neighboring regions of Europe and Northern Africa ( Zohary et al., 2012 ; Mc Govern, 2003 ). During the spreading period via different routes, high genetic diversity among grapevine cultivars is a result of sexual reproduction ( Vouillamoz and Grando, 2006 ), ( Myles et al., 2011 ), and spontaneous mutations ( Margaryan et al., 2021 ). According to Vitis international variety catalog ( Maul and Töpfer, 2015 ), there are more than 12,000 documented grapevine cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…To identify feral types, we performed a parentage analysis between Armenian V. sylvestris and autochthonous cultivated accessions; the dataset from Caucasian wild and cultivated grapes also was used (unpublished data). Cervus 3.0.7 was applied as one of the approaches to screen the material (Margaryan et al, 2021).…”
Section: Plant Materialsmentioning
confidence: 99%
“…The first large-scale study performed by Margaryan et al (2021) focused on genetic diversity and parentage analysis of 492 grapevine genotypes collected across country. The obtained high number of alleles (347 alleles, 14,485 allele/per loci), high level of observed and effective heterozygosity, and presence of female APT3-allele 366, which is absent in western European cultivars, illustrate the huge diversity of the Armenian germplasm.…”
Section: Genetic Diversity and Population Structure Of Wild Grapevine...mentioning
confidence: 99%
See 1 more Smart Citation